Post Keynesian interest rate exogeneity: evidence from Malaysia / Sabri Nayan ... [et al.] - Nayan, Sabri; Kadir, Norsiah; Yusof, Abdul Hafiz; Mohamad Ali, Noor Azillah (2014)
In an economy where money supply is endogenous, interest rate serves as the key instrument of monetary policy. The operation of monetary policy through the setting of a key interest rate and not through a money supply target is actually the fundamental tenet of Post Keynesian economics that money supply is endogenous; that interest rate rather than the stock of money should be the focus of monetary policy. While the proposition of money endogeneity (or interest rate exogeneity) is generally accepted by all Post Keynesians, they disagree on one related question: to what extent are interest rates set exogenously by central banks? While this issue has become the focus of debate between the Horizontalists and Structuralists, the ability of a central bank to influence economic activity would depend much on the interaction between official rate and market rates. The major interest of the present paper is to examine this issue of interest rate transmission mechanism based on the Malaysian data. Employing the cointegration and vector error correction model procedures to analyze the data, results of the study indicate that the pass through from the overnight policy rate to two short term market rates is less than complete.